Attenuation of Mammary Gland Dysplasia and Feeding Difficulties in Tabby Mice by Fetal Therapy - Wahlbuhl, Mandy; Schuepbach-Mallepell, Sonia; Kowalczyk-Quintas, Christine; Dick, Angela; Fahlbusch, Fabian B.; Schneider, Pascal; Schneider, Holm (Journal of Mammary Gland Biology and Neoplasia, 2018)
Hypohidrotic ectodermal dysplasias (HED) are hereditary differentiation disorders of multiple ectodermal structures including the mammary gland. The X-linked form of HED (XLHED) is caused by a lack of the secreted signaling molecule ectodysplasin A1 (EDA1) which is encoded by the gene EDA and belongs to the tumor necrosis factor (TNF) superfamily. Although male patients (hemizygous) are usually more severely affected by XLHED, heterozygous female carriers of an EDA mutation may also suffer from a variety of symptoms, in particular from abnormal development of their breasts. In Tabby mice, a well-studied animal model of XLHED, EDA1 is absent. We investigated the effects of prenatal administration of Fc-EDA, a recombinant EDA1 replacement protein, on mammary gland development in female Tabby mice. Intra-amniotic delivery of Fc-EDA to fetal animals resulted later in improved breastfeeding and thus promoted the growth of their offspring. In detail, such treatment led to a normalization of the nipple shape (protrusion, tapering) that facilitated sucking. Mammary glands of treated female Tabby mice also showed internal changes, including enhanced branching morphogenesis and ductal elongation. Our findings indicate that EDA receptor stimulation during development has a stable impact on later stages of mammary gland differentiation, including lactation, but also show that intra-amniotic administration of an EDA1 replacement protein to fetal Tabby mice partially corrects the mammary gland phenotype in female adult animals.
EVALuna2:35485